The impact of the stratified cognitive apprenticeship model on mathematical motivation in high school students - Ruimei, Wang; Zulkifli, Nurul Nadwa; Mohd Ayub, Ahmad Fauzi (Arts and Science Press, 2024)
This study investigated the impact of a Stratified Cognitive Apprenticeship Model Teaching Module (SCTM) on the mathematical learning motivation of high school students in China. Using a quasi-experimental design, the study was conducted in a high school with 150 ninth-grade students, who were randomly divided into three groups. The first treatment group employed the Cognitive Apprenticeship Model (CAM) teaching strategy, wherein teachers used modelling, coaching, scaffolding, articulation, reflection, and exploration strategies. The second treatment group implemented SCTM teaching, in which students were stratified by their performance ability level and the class was designed following the CAM process. The control group maintained Conventional Instruction (CI), including lectures, note-taking, and homework completion. Motivational assessments were administered to students according to the pretest, post-test, and delayed post-test to evaluate the effects of CAM and SCTM on student learning motivation. The results confirmed through Analysis of Covariance (ANCOVA) demonstrated that the SCTM group outperformed the CAM group, which in turn outperformed the traditional teaching group. These findings provide empirical support for high school mathematics education, proving that teaching strategies combining stratification and the cognitive apprenticeship model can effectively enhance students’ learning motivation. Ethical Compliance: All procedures performed in this study involving human participants were in accordance with the ethical standards of the institutional an national research committee and with the 1964 Helsinki Declaration and its later amendments or comparable ethical standards.